Nppc/Npr2/cGMP signaling cascade maintains oocyte developmental capacity - Celik, Onder; Celik, Nilufer; Ugur, Kader; Hatimaz, Safak; Celik, Sudenaz; Muderris, Iptisam Ipek; Aydin, Suleyman (C M B Assoc, 2019)
The follicle must fulfill the following criteria if it is to survive the period between early embryonic life and the luteinizing hormone (LH) peak. It should (i) be surrounded by pregranulosa cells; (ii) complete the first meiotic division and become dormant; and (iii) continue metabolism during the dormant stage. Interaction between the natriuretic peptide precursor type C (Nppc) and its receptor, natriuretic peptide receptor 2 (Npr2), affects female fertility through the production of oocytes with developmental capacity and maintain oocyte meiotic arrest. While Nppc is expressed in mural cells, cumulus cells express Npr2. Nppc/Npr2 system exerts its biological function on developing follicles by increasing the production of intracellular cyclic guanosine monophosphate (cGMP). This pathway not only contributes to the development of ovary and the uterus, but aids the formation of healthy eggs in terms of their morphological and genetic aspects. A defect in this pathway leads to asmall ovarian size, string-like uterine horns, and thin endometrium and myometrium. Disorganized chromosomes, abnormal cumulus expansion and early meiotic resumption occur in animals with defective Nppc/Npr2 signaling. The types and number of oocytes also decrease when there is incompetent Nppc/Npr2 signaling. This paper extends on most recent and relevant experimental evidence regarding Nppc/Npr2/cGMP signaling with regard to its crucial role in maintaining oocyte meiotic arrest and the production of oocytes with developmental capacity. We further discuss whether the agonist or antagonist forms of the members of this exciting pathway can be usedfor triggering final oocyte maturation.
Keywords: Natriuretic peptide precursor type C (Nppc, CNP); Natriuretic peptide receptor 2 (Npr2, guanylyl cyclase-B); Granulosa cells; Follicle; Oocyte; Meiotic arrest; LH surge; Ovulation trigger